HomeoDB: a database of homeobox gene diversity. - Zhong, Y; Butts, T; Holland, P (2008)
The homeobox genes are a large and diverse group of genes, many of which play important roles in the embryonic development of animals. Comparative study of homeobox genes, both within and between species, requires an evolutionary-based classification. HomeoDB was designed and implemented as a manually curated database to collect and present homeobox genes in an evolutionarily structured way, allowing genes, gene families and gene classes to be compared between species more readily than was possible previously. In its first release, HomeoDB includes all homeobox genes from human, amphioxus (Branchiostoma floridae) and fruitfly (Drosophila melanogaster); additional species can be added. HomeoDB is freely accessible at (http://homeodb.cbi.pku.edu.cn).